Kelemahan Workload Indicatorsof Staffing Need Sebagai Metode Perhitungan Jumlah Kebutuhan Tenaga Kesehatan di Puskesmas - Eska Distia Permatasari; Widodo Jatim Pudjirahardjo (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2015)
ABSTRACT Workload Indicators of Staffing Need (WISN) was a method for calculating the number of health worker in Public Health Center. However, the result from previous studies show that this method had some weakness. Public Health Center in Pacarkeling Surabaya had problem in the shortage of health worker. Previously, Workload Indicators of Staffing Need was applied to assess the health worker. This study identified the weakness of WISN by company to the objective workload. This was an observational study by using total population of medical, midwifery, and nursing staff in Pacarkeling Surabaya Public Health Center. WISN calculation method was performed to get the final result. They were the number of staff needs and the value of ratio. This ratio compared with the result of objective workload calculating to show the weakness of WISN method. WISN method is not appropriate when applied in Public Health Center. There were some weakness in the WISN method that made this method was less accurate. It is because health worker don’t carry out their job based on main duty, the method using data from previous years and don’t pay attention to labor of productivity. Keyword: weakness of WISN, the number of health worker, Public Health                      Center